All Resources Lead to Rome: A Multi-Study Investigation on the Complementary Association of Core Self-Evaluations and Emotional Intelligence on Well-Being - Mérida-López, Sergio; Pekaar, Keri A.; Luque-Reca, Octavio; Extremera-Pacheco, Natalio (Sage, 2025)
This multi-study investigation examined what magnitude of personal resources people need to flourish in their personal life and at work. We specifically looked at the interplay between emotional intelligence (EI) and core self-evaluations (CSE) in relation to flourishing, happiness, and work engagement. Guided by job demands-resources theory, this investigation was conducted through two separate studies (Ns1 = 391; Ns2 = 703) using path analysis with Spanish employees. Study 1 revealed that EI moderated the positive relationship between CSE and flourishing and work engagement so that this relationship was weaker among employees high (vs. low) in EI. Study 2 replicated this pattern for the relationships with happiness and work engagement. Facet-level analyses revealed that use of emotions was driving the moderation on flourishing in Study 1, whereas other-emotion appraisal was driving the moderation on work engagement in Study 2. Overall, these findings suggest that individuals low in CSE might benefit from higher levels of EI to enhance their flourishing. Implications for improving well-being through the development of personal resources are discussed.
https://openpolicyfinder.jisc.ac.uk/id/publication/10322
Keywords: Inteligencia emocional; Autoconcepto; Psicología positiva; Core self-evaluations; Emotional intelligence; Happiness; Flourishing; Work engagement